Breast Cancer Early Detection in Eswatini: Evaluation of a Training Curriculum and Patient Receipt of Recommended Follow-Up Care. (2021) - O'Neil, Daniel S.; Nxumalo, Sifiso; Ngcamphalala, Cebisile; Tharp, G; Jacobson, Judith S.; Nuwagaba-Biribonwoha, Harriet; Dlamini, Xolisile; Pace, Lydia E.; Neugut, Alfred I.; Harris, Tiffany G.
Abstract : PURPOSE: Breast cancer (BC) is detected at late stages in sub-Saharan Africa. We piloted a BC early-detection program in Eswatini aimed at increasing breast health knowledge and clinical skills. We also aimed to determine the proportion of patients with breast abnormalities who completed referral to breast specialty clinics. METHODS: Nurses and counselors from five human immunodeficiency virus and/or antiretroviral therapy clinics underwent training in BC and clinical breast examination (CBE). We compared knowledge and skill examinations completed before, immediately after, and 90 days after training. Nurses then screened female clinic patients ≥ 18 years for breast symptoms, examined those with symptoms, and referred women with CBE abnormalities to a surgeon or the national breast clinic. Consenting women were contacted at 30 and 60 days after screening to determine if they had completed referral. RESULTS: In 2019, 44 nurses underwent training. Median scores (interquartile range) on pretraining, immediate post-training, and 90-day post-training knowledge examinations were 17.5 (16-19), 20 (19-21), and 20 (19-21), respectively. Median scores (interquartile range) on pretraining, immediate post-training, and 90-day post-training skills examinations were 10 (7-11), 23 (21.5-25), and 23 (22-24), respectively. Compared with pretraining scores, post-training scores were significantly improved ( P < .0001 for all comparisons). From June 2019 to April 2020, a total of 9, 502 clinic patients were screened for breast symptoms: 150 (2%) underwent CBE, 93 (62%) were referred for further evaluation, and 88 (97%) were included in the study. Of those, 54 (61%) completed referral. Referral completion was not associated with age, employment, relationship status, or prior experiences related to BC. CONCLUSION: The program's training curriculum improved breast health knowledge and clinical skills. Efforts are needed to improve patients' receipt of recommended evaluation for breast abnormalities.